The Exact Finite Sample Distribution Function of the Limited Information Maximum Likelihood Identifiability Test Statistic - McDonald, James B. (Econometrica, 1972)
[This paper contains the derivation of the exact finite sample distribution function of the LIML identifiability test statistic associated with an overidentified nondynamic structural equation which contains two endogenous variables. Some of the properties of the moments of this statistic are also investigated.]